Carriage of CTX-M-15-Producing Escherichia coli Isolates among Children Living in a Remote Village in Senegal - Ruppé, Etienne (American Society for Microbiology (ASM), 2009)
Two out of 20 children with no known antibiotic exposure, living in a very remote Senegalese village, were found to be fecal carriers of a multiresistant Escherichia coli clone that produced CTX-M-15. This highlights the current massive spread of extended-spectrum β-lactamases, even in isolated communities.